2020
DOI: 10.4236/aid.2020.103009
|View full text |Cite
|
Sign up to set email alerts
|

A Physician Suffering from COVID-19 with Multiple Co-Morbidities Have Delayed Viral Clearance: A Case Report from Bangladesh

Abstract: Background: Novel corona virus (SARS-Coronavirus-2 SARS-CoV-2) which emerged in China has spread to multiple countries rapidly. Little information is known about delayed viral clearance in mild to moderate COVID-19 patients. As it is highly contagious, health care workers including physicians are high risk of being infected in hospital care. Case Report: A 37 years old Bangladeshi physician working in a paediatric unit of a medical college hospital with multiple co-morbidities, hypertension, diagnosed axial sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Most of them mentioned that persistent viremia or delayed viral clearance may be due to weak immunity of the host or absence of innate immunity response to produce antibody [14][15] . Some have mentioned relapse or re-infection as a possibility and some have mentioned mental factors such as post-traumatic stress as a contributing factor [16][17] . Besides, the symptoms after discharge may also be the sequalae of organ damage in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them mentioned that persistent viremia or delayed viral clearance may be due to weak immunity of the host or absence of innate immunity response to produce antibody [14][15] . Some have mentioned relapse or re-infection as a possibility and some have mentioned mental factors such as post-traumatic stress as a contributing factor [16][17] . Besides, the symptoms after discharge may also be the sequalae of organ damage in the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection associated with presence of vascular risk factors such as hypertension, ischemic heart disease, diabetes mellitus and chronic kidney disease [9]. It has been observed that SARS-CoV-2 virus can cause a cytokine storm through ACE-2 receptor binding leading to a hypercoagulable state and increased incidence of vascular thrombosis in patients suffering from COVID-19 [10].…”
Section: Corona Virus Disease 2019 (Covid-19mentioning
confidence: 99%